دور الإذاعة المحلیة في نشر الثقافة المروریة - صحراوي، بوبكر, لخويمس، مصطفى (جامعة الوادي university of Eloued, 2018)
تُعد الإذاعة المحلية وسيلة من وسائل الاتصال الجماهيري، حيث أصبحت تلعب دورًا مهمًا داخل المجتمع من خلال بثها لبرامج اجتماعية وتوعوية، من بينها برامج الثقافة المرورية التي تهدف إلى نشر الوعي المروري بين السائقين. وتمحورت إشكالية الدراسة حول دور الإذاعة المحلية في نشر الثقافة المرورية، وانطلقت من الفرضيات التالية: تقوم الإذاعة المحلية بدور كبير في نشر الثقافة المرورية بين السائقين. تستخدم الإذاعة المحلية أساليب مختلفة في نشر الثقافة المرورية. تؤثر برامج الثقافة المرورية على سلوك السائقين. اعتمدت الدراسة على عينة قصدية مكونة من 6 سائقين من ولاية الوادي، باستخدام المنهج الوصفي، وتم جمع البيانات بواسطة الاستبيان، المقابلة، والملاحظة. وتوصلت الدراسة إلى النتائج التالية: تسهم الإذاعة المحلية في غرس الثقافة المرورية. تحظى الإرشادات والنصائح المرورية باهتمام السائقين. تؤثر برامج التوعية المرورية إيجابيًا على سلوك السائقين. Local radio is considered one of the mass communication tools that plays an increasingly important role in society by broadcasting social and awareness-raising programs, including traffic culture programs aimed at promoting road safety awareness among drivers. The central issue of this study focused on the role of local radio in spreading traffic culture, and it was based on the following hypotheses: Local radio plays a significant role in promoting traffic culture among drivers. Local radio uses various methods to raise traffic awareness. Traffic awareness programs have an impact on drivers' behavior. The study relied on a purposive sample of six drivers from El Oued Province, using the descriptive method. Data were collected through questionnaires, interviews, and observation. The study reached the following conclusions: Local radio contributes to instilling traffic culture. Traffic tips and advice are well received by drivers. Traffic awareness programs positively influence drivers' behavior.
دراسة ميدانية على عينة من السائقين بولاية الوادي
مذكرة ماستر في الإعلام والإتصال
Keywords: الإذاعة المحلية; التوعية المرورية; سلوك السائقين; Local Radio; Traffic Awareness; Driver Behavior